Descriptive Study of Waste Generation and Management in the Joint Lecture Building State University of Malang - Imam Wijayadi; Fitrah Amalia Salim; Rabiatul Adawiyah; Azizah Nur Rochmah; Suhadi Suhadi; Mimien Henie Irawati Al-Muhdhar (Universitas Labuhanbatu, 2025)
Background: The State University of Malang has substantial potential for solid waste generation due to the high density of academic activities. Although general estimates of waste volume are available, detailed data on waste characteristics and composition within campus facilities remain limited. This study aims to quantify waste generation at the food courts of the A19 and A20 Joint Lecture Buildings, evaluate existing waste management practices, and assess the potential for recyclable waste utilization. Methodology: A quantitative descriptive approach was applied. Waste generation measurements were conducted in accordance with the Indonesian National Standard SNI 19-3964-1994 by analyzing waste production and composition over eight consecutive days. Average waste generation per seat, waste volume, and specific gravity were calculated, and waste materials were classified based on their characteristics and sources. Findings: The results indicate daily variations in waste generation, with average rates of 0.14 kg/seat/day at Food Court A19 and 0.07 kg/seat/day at Food Court A20. The dominant waste fractions were paper, plastic, and food waste, reflecting consumption patterns within the study area. Variations in waste volume were associated with fluctuations in academic activities and food service operations. Organic waste shows potential for eco-enzyme production and takakura composting, while paper and plastic waste may be managed through structured collection programs. Contribution: This study provides site-specific empirical data on waste generation rates and composition within a higher education campus, supporting data-driven improvements in campus-scale waste management strategies